Results of distraction and ligamentotaxis in thoracolumbar fractures without decompression - Lingayat, Maruti B.; Sangai, Aman; Ansari, Abdullah (International Journal of Research in Orthopaedics, 2024)
Background: Thoracolumbar fractures are common spinal injuries often requiring surgical intervention. Traditionally, decompression surgery has been used to relieve neural pressure. This study evaluates the effectiveness of ligamentotaxis with pedicular screw fixation, which minimizes the need for decompression, in treating thoracolumbar fractures. Methods: A retrospective cohort study was conducted at a Government Medical College, Aurangabad involving 30 patients aged 18 and older with thoracolumbar fractures treated with ligamentotaxis and pedicular screw fixation. Clinical outcomes were assessed using the visual analog scale (VAS) for pain, the American spinal injury association (ASIA) impairment scale for neurological function, and forward flexion degrees for spinal mobility. Patients were followed up for 12 months post-operatively. Results: Significant pain reduction was observed, with VAS scores decreasing from 8.5 pre-operatively to 2.5 at 12 months (p<0.001). Neurological function improved, with many patients advancing from ASIA category A pre-operatively to category D by 12 months (p<0.001). Spinal mobility showed considerable recovery, with forward flexion increasing from 0 degrees pre-operatively to 80 degrees at 12 months (p<0.001). Conclusion: Ligamentotaxis with pedicular screw fixation is an effective treatment for thoracolumbar fractures, providing substantial pain relief, neurological improvement, and restored spinal function. While outcomes are generally positive, patient selection remains critical to avoid poor neurological results. Further research is needed to refine indications and optimize treatment protocols.